A taxonomy for information privacy in virtual collaborations - Skinner, Geoff; Han, Song; Chang, Elizabeth (WSEAS, 2006)
Privacy is a very diverse field of research and due to its subjective nature, open to many interpretations and representations. Information Privacy forms a key component of Privacy related to research, particularly its importance to Information Technology and the increasing collection and use of personal data. Within any rapidly expanding body of knowledge the terminology used needs to be clearly defined, categorised and relationships established. This paper provides such a taxonomy for Information Privacy. It has evolved through the study and application for information privacy and its affects on the operation, creation, and ongoing administration for Virtual Collaborations. The knowledge provided from an information privacy taxonomy can be used to formulate better information privacy policies, practices, and privacy enhancing technologies (PETs).